Analisis Strategi Pengembangan Hutan Kota Gunung Kembang Sarolangun Di Kabupaten Sarolangun: The Development Strategy Analysis of Gunung Kembang Sarolangun Urban Forest in Sarolangun Regency - Ulfa, Maria; Rana, Rana; Nurmansyah, Rahmad (Jurnal Silva Tropika, 2023)
ABSTRACT The Gunung Kembang Sarolangun City Forest is located in the Sarolangun Regency Government Office Complex. The urban forest was originally a biodiversity park and is included in the green open space area which has an area of 9.8 hectares and is based on the Decree of the Regent of Sarolangun No. 238 of 2022. To maintain the preservation of areas in urban forests, it is necessary to have strategies and policies in urban forests that can function and benefit urban human life in a sustainable manner. Currently, there is no previous research related to the development planning of the Sarolangun City Forest. The purpose of this study is to analyze the development strategy of the Sarolangun Mountain Kembang Urban Forest in Sarolangun Regency. The research was carried out in May 2023 in the Gunung Kembang Sarolangun City Forest and data analysis was carried out at the Forestry Department Laboratory, Faculty of Agriculture, University of Jambi. The data was analyzed descriptively and qualitatively by the SWOT method. The results of the study show that the Gunung Kembang City Forest has been used for various activities such as leisurely walks and selfies. Internal strength factors are the condition of well-maintained urban forests, being a place for the community to gather, good and strategic accessibility, and policy support in urban forest development. Internal weaknesses are minimal budget, lack of research, lack of promotion and low public awareness. External opportunity factors are regional income opportunities, ecosystem-based tourism potential, recreational and camping sites, and support for multi-stakeholder cooperation for urban forest development. External challenge factors are the potential impact of environmental pollution and damage as well as the potential impact of global climate change. The SWOT diagram shows the strategic position that requires internal improvement and the utilization of existing opportunities so that the Gunung Kembang urban forest can be managed properly.   Keywords: development strategy, SWOT, urban forest    ABSTRAK Hutan Kota Gunung Kembang Sarolangun berada di Komplek Perkantoran Pemerintah Kabupaten Sarolangun. Hutan kota awalnya sebagai taman keanekaragaman hayati dan termasuk dalam kawasan ruang terbuka hijau yang memiliki kawasan seluas 9,8 Ha dan berdasarkan SK Bupati Sarolangun No. 238 Tahun 2022. untuk mempertahankan pelestarian kawasan di hutan kota perlu adanya strategi dan kebijakan pada hutan kota yang dapat berfungsi dan bermanfaat bagi kehidupan manusia perkotaan secara berkelanjutan. Saat ini belum ada penelitian terdahulu terkait perencanaan pengembangan Hutan Kota Sarolangun. Tujuan dilakukannya penelitian ini adalah menganalisis strategi pengembangan Hutan Kota Gunung Kembang Sarolangun di Kabupaten Sarolangun. Penelitian dilaksananakn pada bulai Mei 2023 di Hutan Kota Gunung Kembang Sarolangun dan analisis data dilakukan di Laboratorium Juruan Kehutanan Fakultas Pertanian Universitas Jambi. Data dianalisis secara deskriptif dan kualitatif dengan metode SWOT. Hasil Penelitian menunjukkan bahwa Hutan Kota Gunung Kembang telah dimanfaatkan untuk berbagai aktifitas seperti jalan-jalan santai dan swafoto. Faktor kekuatan internal yaitu kondisi hutan kota yang terawat, menjadi tempat masyarakat berkumpul, aksesibilitas yang baik dan strategis, dukungan kebijakan dalam pengembangan hutan kota. Faktor kelemahan internal yaitu anggaran yang minim, kurangnya penelitian, kurangnya promosi dan rendahnya kesadaran masyarakat. Faktor peluang eksternal yaitu peluang pemasukan daerah, potensi wisata berbasis ekosistem, tempat rekreasi dan perkemahan serta dukungan Kerjasama multipihak untuk pengembangan hutan kota. Faktor tantangan eksternal yaitu potensi dampak pencemaran lingkungan dan kerusakan serta potensi dampak perubahan iklim global. Diagram SWOT menunjukkan posisi strategi (turn around) hang menghendaki perbaikan internal dan pemanfaatan peluang yang ada agar hutan kota gunung kembang bisa terkelolan dengan baik.   Kata kunci: hutan kota, strategi pengembangan, SWOT